Impact loading and transient response of pipes transporting gas or liquid - Roslina Mohammad 315862; Kotousov, Andrei, supervisor 562437; School of Mechanical Engineering 513788 (2011)
Thesis (Ph.D) - The University of Adelaide, 2011